2003
DOI: 10.3122/jabfm.16.5.383
|View full text |Cite
|
Sign up to set email alerts
|

Managed Care and Primary Physician Satisfaction

Abstract: Background:We examined whether physician compensation, financial incentives, and care management tools were associated with primary physician job and referral satisfaction. Our study was guided by a conceptual model of physician satisfaction derived from published evidence.Methods: A cross-sectional survey was performed of 495 primary physicians (family practitioners, general practitioners, general internists) in the Seattle metropolitan area in 1997.Results: Bivariate analyses revealed that salary compensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 37 publications
(36 reference statements)
4
48
0
2
Order By: Relevance
“…Greater time spent on administrative tasks has been shown to be associated with low physician job satisfaction independent of compensation, fi nancial incentives, and care management restrictions, 20 while face-to-face patient time has been shown to affect both patient and physician satisfaction. 1,4,20,21 Because physician compensation is generally visit based, the work outside the examination room is largely uncompensated care and may contribute to physicians' dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Greater time spent on administrative tasks has been shown to be associated with low physician job satisfaction independent of compensation, fi nancial incentives, and care management restrictions, 20 while face-to-face patient time has been shown to affect both patient and physician satisfaction. 1,4,20,21 Because physician compensation is generally visit based, the work outside the examination room is largely uncompensated care and may contribute to physicians' dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies carried out in several countries showed that there is a significant correlation between income and job satisfaction [15][16][17] . In a study conducted by Bodur in Turkey, it has been demonstrated that income and working conditions were the most important factors for dissatisfaction of health care providers working at public health centres 1) .…”
Section: Discussionmentioning
confidence: 99%
“…In general, physicians felt not satisfied with these two aspects. This was because the referral system did not work properly and the patient did not follow the referral rules too [18]. The finding showed that in PHCs, people came to primary care to ask referral letter to hospital without doing any examination in the primary care, even it is just coughs, colds, flu, fever, or ordinary colds but directly patients asking for referral to secondary health facilities.…”
Section: Discussionmentioning
confidence: 93%